Development of Malay Culture Student Work Sheet to Improve Student Mathematics Critical Thinking Ability Elementary School - Lili Amelia Putri; Sukmawarti Sukmawarti (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to describe the process of developing mathematical LKPD and determine the quality of the LKPD developed on geometrical material with Malay cultural nuances to improve students' critical thinking skills in learning mathematics. This study uses the Research and Development (R&D) method which is used to produce a product, namely developing LKPD. The development model applied in this study is the ADDIE model which consists of 5 stages, namely analysis (Analyze), design (Design), development (Development), implementation (Implementation), and evaluation (Evaluation). The subjects in this development research were two lecturers as validators consisting of material expert validators and media expert validators, teachers, and 29 students of class V-A as the target of using the product for a limited trial. The type of data used in this research is in the form of quantitative data and qualitative data. The instrument used in this study utilizes a questionnaire and a critical thinking ability test. Based on the results of the trials carried out, it was found that (1) The results of the average acquisition of the two validators namely material experts and media experts for the level of validity were 4.41 on the "Very Good" criteria. (2) The result of obtaining the average teacher response and student response to the LKPD for the practicality level is 4.65 on the "Very Good" criteria. (3) The level of effectiveness of the LKPD is obtained from the average score of the critical thinking ability test, which is 75.86 in the "Good" category and the proportion of students' completeness is 72.41 in the "Good" category. LKPD is good and LKPD is declared effective. The feasibility of LKPD can be seen in the average acquisition of the questionnaire instrument from validators, teachers, and students which is 4.53 with the "Very Eligible" category. It can be interpreted that the LKPD developed can improve students' critical thinking skills in mathematics, especially on geometry material and LKPD is suitable for use by teachers and students because LKPD is valid, practical, and effective.